Respuesta :

Answer:

Option A.

Step-by-step explanation:

The given expression is,

[tex][(64)^{-\frac{1}{2}}]^{-\frac{2}{3}}[/tex]

By solving the given expression,

[tex](64)^{-\frac{1}{2}}=\frac{1}{(64)^{\frac{1}{2}}}[/tex] [Since [tex]a^{-1}=\frac{1}{a}[/tex]]

           [tex]=\frac{1}{\sqrt{64}}[/tex]

           [tex]=\frac{1}{8}[/tex]

Now the expression will be,

[tex][(64)^{-\frac{1}{2}}]^{-\frac{2}{3}}=(\frac{1}{8})^{-\frac{2}{3}}[/tex]

                 [tex]=8^{\frac{2}{3}}[/tex]

                 [tex]={(\sqrt[3]{8})^2}[/tex]

                 = 2²

                 = 4

Therefore, value of the given expression will be 4.

Option (A) will be the answer.

Otras preguntas

ACCESS MORE